Progressive Ataxia, Memory Impairments, and Seizure Episodes in Spna2 R1098Q Mouse Variant Affecting Alpha II Spectrin’s Scaffold Stability - Michał Zalas; Joanna Skrzymowska; Apolonia Miążek; Arkadiusz Miazek (Brain Sciences, 2023)
SPTAN1 spectrinopathies refer to a group of rare, inherited diseases associated with damage to non-erythrocytic α-II spectrin (α-II). They are linked to a range of mild to severe neuropathologies of the central and peripheral nervous systems, such as early infantile epileptic encephalopathy type 5, cerebellar ataxia, inherited peripheral neuropathy, and spastic paraplegia. Modeling human SPTAN1 encephalopathies in laboratory animals has been challenging partially because no haploinsufficiency-related phenotypes unfold in heterozygous Spna2 deficient mice nor stable transgenic lines of mice mimicking missense human SPTAN1 mutations have been created to date. Here, we assess the motor and memory performance of a dominant-negative murine Spna2 (SPTAN1) variant carrying a spontaneous point mutation replacing an arginine 1098 in the repeat 10th of α-II with the glutamine (R1098Q). By comparing groups of heterozygous R1098Q mice at different ages, we find evidence for progressive ataxia, and age-related deterioration of motor performance and muscle strength. We also document stress-induced, long-lasting seizure episodes of R1098Q mice and their poor performance in novel object recognition memory tests. Overall, we propose that the complexity of neuropathology-related phenotypes presented by the R1098Q mice recapitulates a number of symptoms observed in human patients carrying SPTAN1 mutations affecting α-II scaffold stability. This makes the R1098Q mice a valuable animal model for preclinical research.